Reconstructing social theory and the Anthropocene. (February 2017) - Luke, Timothy W
This study reassesses the concept of the Anthropocene as a new geological age as it is influencing contemporary debates in social theory. As a unit of geological time whose changes are allegedly caused, directly and indirectly, by human beings, this scientific concept challenges the existing constructions of theoretical binaries, such as nature/culture, environment/society, objectivity/subjectivity or happenstance/design, in social theory. The analysis suggests many understandings of the Anthropocene in social theory are politicized over-interpretations of natural events, and these moves appear to be developing moral rhetorics of, and operational plans for, managing the Anthropocene to create specific outcomes for those who are the managers as well as the managed. The fact that human beings do not, in fact, have this measure of technical control is ignored by advocates of Anthropocenarian politics to advance their policy agendas.